Cerebral arterial angioplasty in a patient with Loeys–Dietz syndrome. (15th January 2014) - Kellner, Christopher P; Sussman, Eric S; Donaldson, Christopher; Connolly, E Sander; Meyers, Philip M
Abstract : A 14-year-old boy with Loeys–Dietz syndrome (LDS) had an acute neurologic decline 6 days after a subarachnoid hemorrhage. Cerebral angiography at presentation did not show an aneurysmal source of the hemorrhage. However, on post-bleed day 6 the patient experienced an acutely worsening headache and subsequently lost consciousness. Head CT showed new subarachnoid blood and repeat angiography demonstrated a basilar tip aneurysm. Endovascular coil embolization was performed and his neurologic status improved postoperatively until post-bleed day 9 when he became unresponsive. A CT angiogram demonstrated severe proximal vasospasm. After an unsuccessful attempt to treat the vasospasm medically, the patient was transported to the neurointerventional suite for intra-arterial vasodilator treatment, which also failed to ameliorate the vasospasm. The endovascular surgeons were then faced with the conundrum of attempting a high-risk cerebral angioplasty in a pediatric patient with LDS or returning to maximal medical treatment for severe refractory vasospasm.